Некоторые общие вопросы теории термоупругости микрополярных тонких оболочек - С. О. Саркисян (National Academy of Sciences of Armenia)
В работе на основе метода гипотез, который имеет асимптотическую природу, построена прикладная теория термоупругости микрополярных тонких оболочек, выведены уравнения баланса энергии, доказаны энергетические теоремы, построен вариационный функционал этой теории.Thin Shells In the present paper on the basis of the hypotheses method, which has asymptotic nature, applied theory of thermoelacticity of micropolar thin shells is constructed, balance equation is obtained, energetic theorems are proved and variation functional is constructed for this theory. Աշխատանքում ասիմպտոտիկ բնույթ ունեցող վարկածների մեթոդի հիման վրա կառուցված է միկրոպոլյար բարակ թաղանթների ջերմաառաձգականության կիրառական տեսությունը, արտածված է էներգետիկ հաշվեկշռի հավասարումը, ապացուցված են էներգետիկ թեորեմները, կառուցված է այդ տեսության վարիացիոն հավասարումը:
Keywords: Mechanics; Mechanics of deformable solids; Material properties given special treatment